PROFESIONALISME PROFESIONALISME DOSEN DALAM PEMBELAJARAN MATA KULIAH ADMINISTRASI DAN SUPERVISI PENDIDIKAN DI PRODI PAI UIN RADEN FATAH PALEMBANG - Nursalam, Edi; Susilo, Suko; Khoiruddin, Arif (STAI Pelabuhan Ratu, 2025)
This study examines lecturer professionalism in teaching the Administration and Educational Supervision course at the Islamic Education Study Program (PAI) UIN Raden Fatah Palembang. Lecturer professionalism was evaluated through subject mastery, pedagogical competence, effective communication, integrity, and academic ethics. A descriptive qualitative approach with a case study design was employed, involving interviews with lecturers and students, classroom observations, and document analysis. Findings reveal that lecturers deliver material systematically, employ discussion and case study methods, and utilize digital technology to enhance learning. Institutional support such as training, workshops, and learning facilities strengthens professionalism. Main challenges include limited infrastructure, inflexible schedules, and varying student preparedness. The study highlights the need for institutional and pedagogical interventions to improve lecturer professionalism and effective learning based on Islamic values